1995
DOI: 10.1021/j100048a008
|View full text |Cite
|
Sign up to set email alerts
|

Collision-Induced Dissociation of Acrylonitrile Cluster Ions: Geometrical Structure of Polymerized Cluster Anion

Abstract: Collision-induced dissociation (CID) of acrylonitrile (AN: CHFCHCN) cluster cations and anions, (AN),= (n = 2-1 l), with an Ne or Kr atom was investigated in order to elucidate their structures. In the collision of (AN),-with a rare gas atom, [(AN),?-X]-(X = HCN, CH2CN) were produced along with (AN),,-( m I n). The size distributions of the product anions show that (AN),-is composed of a chemically bonded trimeric core anion solvated with chemically bonded AN trimer units and AN monomers. On the other hand, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 3 publications
1
37
0
Order By: Relevance
“…In a previous paper [9], we proposed that oligomerized AN cluster in M(AN) 3 contains a ring geometry, which is assignable to 1,3,5-cyclohexanetricarbonitrile (CHTCN), as reported by Kondow and co-workers [3,[5][6][7][8]. CHTCN is known as a stable species which is prepared from 1,3,5-cyclohexanetricarboxylic acid [22].…”
Section: Magic Numbers Formed By Intracluster Oligomerization Initiatmentioning
confidence: 87%
See 3 more Smart Citations
“…In a previous paper [9], we proposed that oligomerized AN cluster in M(AN) 3 contains a ring geometry, which is assignable to 1,3,5-cyclohexanetricarbonitrile (CHTCN), as reported by Kondow and co-workers [3,[5][6][7][8]. CHTCN is known as a stable species which is prepared from 1,3,5-cyclohexanetricarboxylic acid [22].…”
Section: Magic Numbers Formed By Intracluster Oligomerization Initiatmentioning
confidence: 87%
“…Also in the present M(AN) n clusters, the observed magic numbers can be related with the intracluster electron transfer from alkali metal atom followed by oligomerization of AN. In fact, in the detailed studies of (AN) − n ions by Kondow and co-workers [3,[5][6][7][8], n = 3 and 6 are found to be magic numbers. These stable species are concluded to be produced by intracluster oligomerization after electron attachment to (AN) n [3,[5][6][7][8].…”
Section: Magic Numbers Formed By Intracluster Oligomerization Initiatmentioning
confidence: 98%
See 2 more Smart Citations
“…8 Collision-induced dissociation shows that [(AN) m CN] -(m ) 3, 6) are efficiently produced from (AN) n -(n ) 6, 9). The authors of ref 8 claim that the CHTCN units are held together through a CN group in the cluster anions.…”
Section: Oligomerization Reactions Of Chtcnmentioning
confidence: 99%